ESTUDO TEÓRICO DA INTERAÇÃO DO OXIGÊNIO MOLECULAR COM OS COMPLEXOS DE DIBENZOTETRAAZA[14]ALUNENO DE FERRO (II) E MANGANÊS (II) - Costa, Hawbertt Rocha (2012)
This work presents computational studies of complexes of Fe (II) TAA and Mn (II) TAA using calculations based on density functional theory (DFT). Thus, Fe (II) TAA and Mn (II) TAA, with various multiplicities, were optimized and a comparative study with experimental data was conducted to investigate the distances and bond angles as well as other parameters such as the total energy and the frontier orbitals (HOMO-LUMO). In addition, we also carried out calculations of these complexes with molecular oxygen adsorbed in order to analyze the catalytic behavior for the oxygen reduction reaction. Thus, the lower binding energy and vibrational frequencies of the complex of Fe (II) TAA gave it a higher catalytic activity for this purpose.